Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1144/gsl.sp.1996.101.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Chron C25n in the upper Paleocene Upnor Formation of the London Basin, UK

Abstract: Lithostratigraphic studies of four borehole cores drilled through the late Paleocene Lambeth Group (Upnor, Woolwich and Reading Formations) and basal London Clay Formation of central London have been supplemented with palaeomagnetic, calcareous nannoplankton and palynological data. The Woolwich and Reading Formations and the lower London Clay Formation are reversely magnetized and were deposited during the early part of Chron C24r. The first record of both NP9 and Chron C25n, hitherto missing from the Paleogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Its occurrence in the UK can now be delineated more accurately. It has already been recorded at Cobham , Upnor (Powell et al, 1996) and the Jubilee 404T borehole (Ellison et al, 1996) in the lower shelly clays of the Woolwich Formation. It cannot be confused with acmes associated with later hyperthermals as the oldest of these, ETM2 (or ELMO) occurs at ,53.6 Ma near the end of Chron C24r in calcareous nannoplankton Zone NP11 (Lourens et al, 2005).…”
Section: Evidence From the Apectodinium Acmementioning
confidence: 85%
See 1 more Smart Citation
“…Its occurrence in the UK can now be delineated more accurately. It has already been recorded at Cobham , Upnor (Powell et al, 1996) and the Jubilee 404T borehole (Ellison et al, 1996) in the lower shelly clays of the Woolwich Formation. It cannot be confused with acmes associated with later hyperthermals as the oldest of these, ETM2 (or ELMO) occurs at ,53.6 Ma near the end of Chron C24r in calcareous nannoplankton Zone NP11 (Lourens et al, 2005).…”
Section: Evidence From the Apectodinium Acmementioning
confidence: 85%
“…12) in a succession resembling that of the Cobham Lignite Bed and lower Woolwich shelly clays at Cobham. Independent correlation of the Paris Basin carbon isotope negatives and positives with the UK succession in the Jubilee 404T borehole in London (Thiry et al, 1998) has identified N1 near the top of the lower wedge of the Reading Formation, immediately below the base of the Woolwich Formation, which contains the Apectodinium acme (Ellison et al, 1996). The N1 spike in the 404T borehole is in exactly the same position with respect to the base of the Woolwich Formation as is the Cobham Lignite Bed at Cobham.…”
Section: Evidence From Position Of the Cie Elsewhere In Northwest Europementioning
confidence: 99%
“…Arrows with magnetochrons and NP zones near the Upnor column indicate records further east. Sources for the site logs: Bone (1986), Brown and Wrigley (1925), Collinson (personal observation), Davis (1928), Dewey and Bromehead (1921), Dines et al (1954), Ellison et al (1996), Hooker (personal observation), Kennedy and Sellwood (1970), Klaassen (1883), Pitcher et al (1958), Rundle (1972), Skipper (1999), Tracey (1986), Whitaker (1889Whitaker ( , 1908Whitaker ( , 1912 HCl, followed by 5% potassium hydroxide if necessary, then rinsing in water. In most cases potassium hydroxide treatment resulted in excellent lignite disaggregation as reported by Allen (1982) for most Cobham Lignite samples.…”
Section: Methodsmentioning
confidence: 99%
“…Samples with less than 5% carbon were excluded as un reliable. strata belonging to C24r (Ellison et al, 1996). The Cernaysian European Land Mammal Age (ELMA) is present in the upper reversed (C24r) interval of the Upnor Formation, 45 km east of Upnor at Herne Bay (Hooker and Millbank, 2001).…”
Section: Chronological Context Of the Cobham Lignite Bed And Potentiamentioning
confidence: 99%
“…The Upnor Formation-sand and mud unit junction is incised, marking the Th4-5 sequence boundary (Collinson et al 2003) and predating the Palaeocene-Eocene boundary by c. 80 ka (Hardenbol et al 1998). The Apectodinium acme (a proxy for the PETM interval in paralic and marine environments; see Collinson et al (2003) for discussion) is recorded from the lower Woolwich Shell Beds at the nearby site of Upnor, Kent (Powell et al 1996), in the Jubilee Line 404T borehole, London (Ellison et al 1996) and at Newhaven, East Sussex (Dupuis & Gruas-Cavagnetto 1985). hence the onset of the PETM.…”
mentioning
confidence: 99%